Basic kitchen preparation. - 4 0 16; Culinary Institute of America; 5 Culinary Institute of America (New York, 2007)
Provides the fundamental techniques required to succeed in the professional kitchen while gaining a thorough understanding of ingredients and flavors. All chefs can benefit from improving their skills and increasing their production{u2014}and in this DVD, you'll learn 30 fundamental culinary techniques guaranteed to help you do both. Basic Kitchen Preparation brings you both traditional and contemporary methods straight from the classrooms and kitchens of the CIA, including: vegetable preparation{u2014}dicing and chopping, garlic and shallot roasting, and techniques using tomatoes, mushrooms, peppers, chiles, herbs, artichokes, and asparagus ; flavor enhancers{u2014}mirepoix and matignon, bouquet garni and sachet d'epices, brines, barbecue, marinades, dry rubs, and clarifying butter ; ingredient Preparation and Handling{u2014}whipping cream and egg whites, rehydrating beans and fruits, folding, tempering, and pan-toasting.
DVD format.
Keywords: 2 -- 0; 6; Kitchen.;Cookery. -- 20; 20; 2